2010
DOI: 10.1007/s12078-010-9078-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Pleasant Ambient Fragrances on Dental Fear: Comparing Apples and Oranges

Abstract: Previous studies showed that orange odor reduces the anticipatory anxiety and improves the mood of patients waiting for scheduled appointments in small dental practices. We replicated these previous studies in the setting of three large dental clinics. In addition, we investigated whether another pleasant fruity smell (apple odor) is similarly associated with reduced anxiety. We included 219 patients (117 males, 102 females) between the ages of 18 and 81 in this study. While they were waiting for dental treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 55 publications
2
27
0
2
Order By: Relevance
“…Consistent with the findings of our study, there are studies that also reported no significant psychological effects of aroma administration [2,11,14,15].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Consistent with the findings of our study, there are studies that also reported no significant psychological effects of aroma administration [2,11,14,15].…”
Section: Discussionsupporting
confidence: 92%
“…A study demonstrated reduced tension and anxiety with apple [7], however no significant effect of apple on anxiety or mood were reported in another one [11]. Two studies showed anxiolytic effects of chamomile [12,13], but no significant effect on anxiety was observable in another study using chamomile [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…recommended that aromatherapy can be more useful at a moderate level of anxiety;[27] however, in a study conducted by Toet et al ., the use of orange and apple odors did not reduce anticipatory anxiety and did not improve mood of patients waiting for scheduled visits in large dental clinics. [28] In a study performed by Maura et al ., the effect of gender and ethnicity on preferences and attitudes in children was investigated. They reported that children are very different from adults in their odors and taste preferences and they are likely to use essential oils which they find pleasant.…”
Section: Introductionmentioning
confidence: 99%
“…Los aromas cítricos son los de mayor uso (Lehrner et al, 2000;Chebat y Michon, 2003;Lehrner et al, 2005;Gueguen y Petr, 2006;Chebat et al, 2008;Toet et al, 2010;Schiffers-tein, et al, 2011;Teller y Dennis, 2012;Doucé y Janssens, 2013;Herrmann et al, 2013). Por otro lado, aunque en la mayoría de estudios se utilizaron aromas sin identificar si eran de tipo comercial u odotipo (Hirsch, 1995;Gueguen y Petr, 2006;Spangenberg et al, 2006;Parsons, 2009;Walsh et al, 2011;Clarke et al, 2012;Lunardo, 2012;Doucé y Janssens, 2013), se destaca que los aromas de tipo comercial suelen ser en su mayoría frutales o naturales, aunque también existen aromas que simulan el olor de alimentos preparados como galleta o pan recién horneado (Parsons, 2009;Lunardo, 2012).…”
Section: Análisis De Las Aplicaciones Y Sus Efectosunclassified